2017
DOI: 10.1016/j.addr.2017.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Progress in tumor-associated macrophage (TAM)-targeted therapeutics

Abstract: As an essential innate immune population for maintaining body homeostasis and warding off foreign pathogens, macrophages display high plasticity and perform diverse supportive functions specialized to different tissue compartments. Consequently, aberrance in macrophage functions contributes substantially to progression of several diseases including cancer, fibrosis, and diabetes. In the context of cancer, tumor-associated macrophages (TAMs) in tumor microenvironment (TME) typically promote cancer cell prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
484
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 642 publications
(524 citation statements)
references
References 227 publications
6
484
0
Order By: Relevance
“…[1,2] Therefore, a comprehensive understanding of how the immunosuppressive tumor microenvironment develop is critical and regarded as a promising direction of intervention. [4] Macrophages are known for their vital role in immune defense against the foreign pathogens to prevent tumorigenesis. [3] This versatile cell type displays remarkable plasticity with opposite effects on cell survival, immune responses, and angiogenesis, causing overall pro-or antitumor outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] Therefore, a comprehensive understanding of how the immunosuppressive tumor microenvironment develop is critical and regarded as a promising direction of intervention. [4] Macrophages are known for their vital role in immune defense against the foreign pathogens to prevent tumorigenesis. [3] This versatile cell type displays remarkable plasticity with opposite effects on cell survival, immune responses, and angiogenesis, causing overall pro-or antitumor outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…[3] This versatile cell type displays remarkable plasticity with opposite effects on cell survival, immune responses, and angiogenesis, causing overall pro-or antitumor outcomes. [4,6] Moreover, the increased infiltration of M2-like TAMs also provides a protumor immunosuppressive milieu by altering recruitment and function of leukocytes, such that it is associated with therapeutic failure and poor clinical prognosis in almost all tumors. [5] However, an increasing number of studies indicated that TAMs skew from proinflammatory M1-like phenotype in early stages of some tumors toward the anti-inflammatory M2-like phenotype in most advanced tumors, promoting the tumor growth, angiogenesis, and metastasis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4–6 Significant attention has therefore been drawn towards development of anti-cancer immunomodulating therapies targeting M2-TAMs in order to lower the relative M2-to-M1 abundance and restore the tumoricidal microenvironment. 7,8 …”
mentioning
confidence: 99%
“…iNOS and CD163 are the markers of M1 and M2, respectively [15]. It is well known that TAMs typically promote cancer cell proliferation, immunosuppression, and angiogenesis in support of tumour growth and metastasis [16,17]. Numerous studies have shown that cancer tissues with high infiltration of TAMs are associated with resistance to therapies and poor patient prognosis [18,19].…”
Section: Introductionmentioning
confidence: 99%